Financial Management Model and Increasing the Independence of UMKM in Ponorogo - Marsiwi, Dwiati; Winanto, Asis Riat; Pinaryo (Jurnal Ekonomi dan Bisnis Digital, 2024)
Small, Micro and medium business activities are currently experiencing good development, especially in the food and beverage sector. Therefore, MSMEs must also be able to manage finances by preparing good financial reports. Financial management and reporting in MSMEs is still not widely used. This is because MSMEs feel that their daily money turnover can be predicted. However, without recording and separating personal assets from his business, an entrepreneur cannot control his business properly. The mixing of personal interests with business can increase risks to business sustainability and continuity. The independence of small, micro and medium enterprises today is the ability to run their business only by relying on their own capital. Soft loan capital is very rarely obtained because financial management has not been carried out, so even simple financial reports are not available. Business independence of course needs to be accompanied by the ability of MSMEs to manage their finances.